Transferring Key Success Factors from Ambulatory Care into the Community Pharmacy in the United States - Alex J. Luli; Linda Awdishu; Jan D. Hirsch; Jonathan H. Watanabe; Mark Bounthavong; Candis M. Morello (MDPI AG, 2021)
In the United States, pharmacists' scope of practice continues to expand, with increasing opportunities for pharmacists in all practice settings to enhance health in society. In ambulatory care, pharmacists remain integral members on the healthcare team and have demonstrated positive impacts on patient care. Sharing similar characteristics as pharmacists in the community setting, a deeper look into common elements of a successful ambulatory care practice that can be applied in the community pharmacy setting is warranted. Key success factors identified from ambulatory care include (1) maximizing a pharmacist's unique knowledge base and skill set, (2) forming collaborations with physicians and other providers, (3) demonstrating outcomes and value, and (4) maintaining sustainability. Opportunities exist for pharmacists in the community setting to utilize these success factors when developing, implementing, and/or expanding direct patient care services that improve accessibility to quality care and population health.